Adsorption/desorption of biomacromolecules involved in catalytic hydrogen evolution - Strmečki, Slađana; Paleček, Emil (Bioelectrochemistry, 2018)
Previously, it has been shown that proteins and some polysaccharides (PSs) catalyse hydrogen evolution, producing electrochemical signals on mercury electrodes. The catalytic hydrogen evolution reaction (CHER) of the above-mentioned biomacromolecules was studied by voltammetric and chronopotentiometric stripping (CPS) methods. To obtain more information about electrode processes involving CHER, here we used protein such as BSA, and chitosan as a PS; in addition, we investigated dextran as a control PS not involved in CHER. We studied biomacromolecules by phase-sensitive alternating current (AC) voltammetry. Using phase-in AC voltammetry, for CHER-involved biomacromolecules we observed a CHER peak at highly negative potentials, similar to that observed with other voltammetric and CPS methods. On the other hand, by means of the adsorption/desorption processes studied in phase-out AC voltammetry, we uncovered a sharp and narrow decrease of capacitive current in the potential range of the CHER peak, denominated as the tensammetric minimum. This minimum was closely related to the CHER peak, as demonstrated by similar dependences on specific conditions affecting the CHER peak such as buffer capacity and pH. A tensammetric minimum was not observed for dextran. Our results suggest specific organization of biopolymer layers at negative potentials observed only in biomacromolecules involved in CHER.
Keywords: Cattle; konduktometrie; Animals; skot; Catalysis; vodík; katalýza; Adsorption; rtuť; sérový albumin hovězí; chitosan; Serum Albumin, Bovine; Chitosan; Dextrans; dextrany; Conductometry; Mercury; Hydrogen; Electrodes; Helix (hlemýždi); Helix, Snails; elektrody; zvířata; konkanavalin A; Concanavalin A; adsorpce